Analysis of Consistency The REEDA Scale in Healing Second-Degree Perineal Lacerations - Yuniarti Yuniarti; Noor Pramono; Bambang Cahyono; Agnescia Clarissa Sera (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Many studies of perineal wounds use the redness, edema, ecchymosis, discharge, and approximation (REEDA) scale as a healing assessment tool. Still, this tool has not become part of the standard of care in postpartum women with perineal lacerations due to the lack of evidence of its validity. This study aimed to analyze the consistency of the REEDA scale in healing perineal wounds of postpartum women. The method uses an observational study using the interrater reliability test for the REEDA tool on perineal wound healing in postpartum women with second-degree perineal lacerations, 11 women were recruited using consecutive sampling. Lacerations were observed by researchers, and midwives were trained on days 1, 3, and 7 postpartum. Cohen's kappa coefficient test was used to test the consistency of the REEDA scale. The results shows that the fair and excellent agreement on the redness item with kappa (0.57-1.00), agreement on the edema item showed good and excellent results (0.61-0.84), fair and good agreement on the ecchymosis item (0.51- 0.73), good and excellent agreement on discharge items (0.79 -1.00). On the approximation item (0.62–1.00), agreement improved to excellent at the final assessment. In the third evaluation, the scoring of all items showed good or excellent agreement between the raters. The conclusion is the overall assessment shows that the application of the REEDA scale is reliable because it shows consistency; namely, there are no more values with low agreement on the seventh day of the postpartum period.